Entry splash suppressing techniques in modern competitive diving - Karpov, V. Yu.; Raspopova, E. A.; Stepanova, O. N.; Kurkin, P. E. (Theory and Practice of Physical Culture, 2018)
Dives in modern competitive diving are scored by approach, flight and entry, with the divers entering water mostly in the head-first position in contrast to many other sport disciplines. A perfect splash-free "rip" entry is critical for a highly scored dive, and that is the reason why such high priority in the modern training systems is given to this very dive element. The amount of splash is controllable by a variety of entry techniques to be mastered for a competitive success. The article considers the splash-control pre- and post-entry (underwater) techniques applicable in the dives with back and front rotations. The authors conclude that the entry quality upon the front/back rotation dive is largely determined by body shape, line and pre-and post-entry actions.